Translation Classics in Context (Taylor & Francis, 2025)
Translation Classics in Context carefully considers the relationship between translation and the classics. It presents readers with revelatory and insightful case studies that investigate translations produced as part of nexuses of colonial resistance and liberation across Africa and in Ireland; translations of novels and folklore collections that influence not just other fictions, but stage productions and entire historical disciplines; struggles over Ukrainian and Russian literature and how it is shaped and transferred; and the role of the academy and the curriculum in creating notions of classic translations. Along the way it covers oral poetry, saints, scholars, Walter Scott and Jules Verne, not to mention Leo Tolstoy and the Corpse Bride making her way from folklore to Frankenstein and into the world of Disney animation. Contributors are all leading scholars, and the book is accessible and engaging, assuming no specialist knowledge. Chapter 6 of this book is freely available as a downloadable Open Access PDF at http://www.taylorfrancis.com under a Creative Commons Attribution-Non Commercial-No Derivatives (CC-BY-NC-ND) 4.0 license.